Legal Certainty in Question: Oral Employment Agreements and the Protection of Film and Advertising Talent Coordinators - Nabila Adelita; Aurora Jillena Meliala (Lambung Mangkurat Law Journal, 2026)
In the Indonesian film and advertising industries, freelance roles such as talent coordinators typically operate under project-based work arrangements governed by verbal employment agreements. This study addresses that gap by analysing how normative inconsistencies translate into everyday practices of precarity. Using a normative–empirical legal approach with purposive sampling, this study draws on in-depth interviews with talent coordinators and analysis of labour regulations. Daniel Little’s causal mechanism framework is applied to explain how the absence of written contracts functions as an institutional mechanism that weakens enforceability and normalises violations of labour standards. The findings show that 100 per cent of informants experienced the denial of basic labour rights guaranteed under Indonesian law, including regulated working hours, overtime consent, and compensation. This study demonstrates that regulatory flexibility without institutional safeguards does not enhance adaptability but instead produces structured vulnerability for freelance workers. It contributes to the literature by linking regulatory design to concrete mechanisms of rights erosion in the creative sector. The study concludes by proposing a shift from permissive flexibility towards a model of responsive regulation through the introduction of standardised digital contracts and strengthened labour oversight as prerequisites for film production licensing, thereby offering a transformative pathway to reduce precarity while maintaining industrial flexibility.